Ácido úrico e fatores de risco cardiovasculares no final da infância e início da adolescência - Peçanha, Marcos Alves de Souza (2018)
The aim of this study was to investigate the relationship between uric acid and cardiovascular risk factors at the end of childhood (8-9 years) and early adolescence (10-14 years), of schoolchildren in the region of Maruípe in the municipality of Vitória-ES. This is a cross-sectional, observational, convenience study with 296 children and adolescents, of both sexes, from 9 public schools in the city of Vitória-ES. Anthropometric, hemodynamic and biochemical assessments were performed (Fasting of 12 h), blood collection was used to determine fasting glycemia, plasma insulin, total cholesterol and fractions (HDL and LDL), triglyceride plasmatic (TGC), uric acid (UA), plasma insulin, C-reactive protein and total leukocytes. Insulin resistance was evaluated by calculating the HOMA-IR index. Measurements of weight, height, waist circumference (WC), hip perimeter (HP) and body fat percentage (%BF) were obtained. In the evaluation for uric acid, the values above the 90 percentile were considered high according to each phase and sex. Statistical analyses were performed using the Kolmogorov-Smirnov test, chi-square test or Fischer exact test, Mann Whitney test, Pearson or Spearman correlation, and simple and multiple logistic regression models. The significance level adopted was p < 0.05. The project was approved by the Ethics Committee on Research with human beings of the Federal University of Espírito Santo (Opinion n° 1.565.490) and the term of free and informed consent was signed by the participants and their guardians. It was observed that the sample consisted of 54,4% (n = 161) Females, with mean age 10,7 ± 2,0 years and 54,0% (n = 159) were adolescents. When assessing the prevalences of anthropometric inadequacies and body composition according to the uric acid classification according to the phases, both in childhood and adolescence, overweight, WC, HP, waist-to-height ratio (WHR) and excess body fat showed higher prevalence in relation to elevated uric acid, and in biochemical and clinical alterations. In childhood, significance was manifested in HDL, insulin and insulin resistance, and in adolescence with blood pressure, LDL, insulin and insulin resistance. The correlation between uric acid levels and body composition, biochemical and clinical, were moderate in childhood with weight, WHR, HP, %BF, and negatively with HDL. Simple regression in childhood indicated that BMI, WC, HP, WHR, %BF, elevated Homa-IR index and low HDL, and in adolescence BMI, HP, WHR, %BF, blood pressure (BP), LDL and Homa-IR index showed a higher chance of presenting elevated uric acid. In the multiple logistic regression model for removal of the effect, it was observed that no variable remained associated. It was concluded that children and adolescents with elevated uric acid did not present association for cardiovascular risk factors. However, higher uric acid values were noted in the individuals evaluated with inadequate anthropometric and body composition parameters.